SOCIAL PARADIGM OF LAW - Oana Andra NIȚĂ (International Journal of Social and Educational Innovation)
The need for a coherent framework of rules in the life of the citizen and the environment which he lives in is a fundamental element, being an important premise for the free and healthy development of society. The natural expectations of the individual are to ensure a safe life, enjoy high-quality health and education system, ensure public order etc. All these living conditions can be offered only by the form of social system, which is a form of organization that men preferred to embrace when they decided to give up their original freedom. Consequently, the state institutions are the ones that have the decisive role in achieving the legislative framework of a society. Thus, the adoption of normative acts must be based on the principle according to which society is not governed by arbitrary decisions of the members of the state administration, but by the law.